2017
DOI: 10.1021/acsami.7b08563
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Prediction of Surface Stability and Morphology of LiNiO2 Cathode for Li Ion Batteries

Abstract: Ni-rich layered oxides are considered to be a promising cathode material with high capacity, and their surface structure should be extensively explored to understand the complex associated phenomena. We investigated the surface stability and morphology of LiNiO as a representative of these materials by using density functional theory calculations. The results reveal that the Li-exposed surfaces have lower energies than the oxygen surfaces, irrespective of the facets, and the Ni-exposed ones are the least stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 61 publications
6
60
0
1
Order By: Relevance
“…In LNO, the Ni content is higher and so is the reactivity. Indeed, recent computational results revealed that polar facets with exposed oxygen lower the Fermi energy of the material, thereby facilitating electron transfer from the electrolyte . The same authors also showed that, in general, Ni‐exposed surfaces are the least stable ones, while Li‐exposed ones are the most stable.…”
Section: Challengesmentioning
confidence: 95%
“…In LNO, the Ni content is higher and so is the reactivity. Indeed, recent computational results revealed that polar facets with exposed oxygen lower the Fermi energy of the material, thereby facilitating electron transfer from the electrolyte . The same authors also showed that, in general, Ni‐exposed surfaces are the least stable ones, while Li‐exposed ones are the most stable.…”
Section: Challengesmentioning
confidence: 95%
“…[7,80] Specifically, a stoichiometric amount of aluminum isopropoxide (≥99.99%, Sigma-Aldrich) was dissolved in isopropanol solvent (99.7%, Sigma-Aldrich) at 60 °C and then mixed with the Ni 0.94 Co 0.06 (OH) 2 precursor with magnetic stirring until the solution was dried to yield Al(OH) 3 , and poly(vinylidene) fluoride (PVDF) (HSV900, ≥99.5%, MTI Corp.) with a mass ratio of 8: 1: 1 were mixed in N-methyl-2-pyrolidone (NMP) (99%, Sigma-Aldrich) under vigorous stirring to form a black slurry. [7,80] Specifically, a stoichiometric amount of aluminum isopropoxide (≥99.99%, Sigma-Aldrich) was dissolved in isopropanol solvent (99.7%, Sigma-Aldrich) at 60 °C and then mixed with the Ni 0.94 Co 0.06 (OH) 2 precursor with magnetic stirring until the solution was dried to yield Al(OH) 3 , and poly(vinylidene) fluoride (PVDF) (HSV900, ≥99.5%, MTI Corp.) with a mass ratio of 8: 1: 1 were mixed in N-methyl-2-pyrolidone (NMP) (99%, Sigma-Aldrich) under vigorous stirring to form a black slurry.…”
Section: Methodsmentioning
confidence: 99%
“…In LNO ist der Ni‐Gehalt höher und damit auch die Reaktivität gegenüber dem Elektrolyten. Tatsächlich ergaben jüngste Rechnungen, dass polare Facetten mit freiliegendem Sauerstoff die Fermi‐Energie des Materials senken und den Elektronentransfer aus dem Elektrolyten erleichtern . Die gleichen Autoren zeigten auch, dass im Allgemeinen Ni‐exponierte Oberflächen die am wenigsten stabilen sind, Li‐exponierte Oberflächen hingegen die stabilsten.…”
Section: Herausforderungenunclassified